Comparing Narx and Narmax Models Using Ann and Svm for Cash Demand Forecasting for Atm - Acuna-Leiva, G (2012)
A comparative study between NARMAX and NARX models developed with ANN and SVM when used to forecast cash demand for ATMs is conducted. A simple methodology for developing SVM-NARMAX models is proposed. The best results were obtained with NARX-ANN models. In addition no significant differences were found between NARX and NARMAX for both ANN and SVM. Hence it seems advisable to choose simpler models, such as NARX and a user-friendly tool like ANN at least for this particular application. © 2012 IEEE.